THE USE OF TRILINGUAL QURAN TO IMPROVE THE STUDENTS’ VOCABULARY AT THE TENTH GRADE STUDENTS OF ISLAMIC BOARDING SCHOOL OF BABUL KHAER BULUKUMBA - Putri, Alfridha Dwi; Bakri, Irfiani; Fisma, Fisma (Institut Agama Islam Negeri (IAIN) Bone, 2024)
This study examines the effectiveness of using the English translation of the Quran as an educational medium to enhance vocabulary acquisition among tenth-grade students at Babul Khaer Islamic Boarding School, Bulukumba. By applying a pre-experimental design with pre-test and post-test assessments, the study aims to explore vocabulary gains facilitated through the contextual guesswork technique. This approach not only aids students in understanding word meanings by referencing both Indonesian and English translations but also supports character education by incorporating moral values in language learning. Results reveal significant improvement, with the average vocabulary score increasing from 49.64 in the pre-test to 70.16 in the post-test. Statistical analysis supports these findings, with a t-test result of 13.31 exceeding the t-table value of 2.074, confirming the alternative hypothesis that Quranic English translation can significantly improve vocabulary. The study suggests that the Quran’s English translation serves as an effective medium for vocabulary acquisition and offers valuable insights for enhancing vocabulary improvement in EFL contexts. These findings contribute to the educational media approach in Islamic boarding school settings and provide a foundation for future research in similar environments